Integrative science in practice : Process perspectives from ASB, the partnership for the tropical forest margins - Tomich, Thomas P.; Timmer, D.W.; Velarde, S.J.; Alegre Orihuela, JC; Areskoug, V.; Cash, D.W.; Cattaneo, Andrea; Ericksen, Polly J.; Joshi, L.; Kasyoki, J; Legg, C.; Locatelli, M.; et al. (Elsevier, 2007)
ASB, the Partnership for the Tropical Forest Margins, is a decade-old, complex, multi-institutional, multi-disciplinary, multi-site research and development consortium. It has been recognized for its success in producing scientific outputs and real world impacts and as a pioneer in integrated natural resource management (iNRM). Until now, there has been little understanding of the reasons for its success in integrating different perspectives and ways of working. To fill this gap, an on-line consultation involving ASB researchers was structured following an analytical framework developed by the Initiative on Science and Technology for Sustainability. The structure of the presentation of major results presented in this article also follows that framework, which includes four dimensions of integration (disciplinary, functional, spatial/temporal, and knowledge) and linked challenges of institutional learning and adaptation, fostering appropriate participation, and managing resource and capacity constraints. To lay the foundations for interpreting these insights and to motivate the study, introductory sections present qualitative evidence regarding organizational learning within the consortium (using research hypotheses as indicators) and success in producing integrated results (using a selection of research results as evidence).